Human dignity and human rights - Shaibakova, Kamila Danilovna (Opción, 2019)
The article answers the questions of what human dignity is and why it is important via ethical theories. As a result, the central idea regarding the concept of human dignity in the German constitution is the renouncement of the Nazi past and the grave human rights abuses that characterized it. In the shadow of the Holocaust, lawmakers made dignity the cornerstone of Germany’s legal architecture binding all three powers. In conclusion, human dignity and human rights are inseparable, and in order to be accepted as a human right, it shall have a strong link with dignity.